2022
DOI: 10.17925/usn.2022.18.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations of SARS-CoV-2 Infection and the Role of Complement Activation

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, while considered a respiratory illness, is associated with a wide range of neurological manifestations, with severity ranging from transient deficit to permanent disability and death. These neurological manifestations can be divided into central nervous system complications, which include cerebrovascular disease and encephalopathies, and peripheral nervous system complications, which involve the muscle (i.e. muscle injuries, myositis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Therefore, our research raises the possibility that phenothiazines may target additional host receptors or co-receptors, such as dopamine, to modulate cellular entry of SARS-CoV-2. It has been reported that the infection of SARS-CoV-2 is associated with a wide range of neurological manifestations, including encephalopathy, encephalitis, cerebrovascular disease, and headaches [ 49 , 50 ]. Phenothiazines may also be effective in inhibiting SARS-CoV-2 infection in the central nervous system, thus preventing long-term neuronal damage and effectively reducing morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our research raises the possibility that phenothiazines may target additional host receptors or co-receptors, such as dopamine, to modulate cellular entry of SARS-CoV-2. It has been reported that the infection of SARS-CoV-2 is associated with a wide range of neurological manifestations, including encephalopathy, encephalitis, cerebrovascular disease, and headaches [ 49 , 50 ]. Phenothiazines may also be effective in inhibiting SARS-CoV-2 infection in the central nervous system, thus preventing long-term neuronal damage and effectively reducing morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the role of complement in the pathogenesis of the Zika virus in the CNS has been shown in mouse models [91]. Recent reports have also highlighted the key role of complement activation in the development of neurological manifestations following SARS-CoV-2 infection [92,93]. Importantly, studies in both animal models and human brain tissue indicate that the impairment of complement regulation may contribute to AD pathogenesis [22,23,26,33,63,[65][66][67].…”
Section: Complement Systemmentioning
confidence: 99%
“…Dysregulation of the complement system in the CNS contributes to various neurological disorders, including neurodevelopmental disorders such as autism and schizophrenia (Brown, 2012) (Sekar et al, 2022) (Yilmaz et al, 2021), neurodegenerative diseases, diseases associated with disturbances in blood-brain barrier (BBB) functions, etc. Additionally, recent research has demonstrated the critical role of complement cascade in the development of neurological complications of SARS-CoV-2 infection (Jaffry et al, 2022) (M. H. Lee et al, 2022).…”
Section: Complement Proteinsmentioning
confidence: 99%